Implementasi Enkripsi Vernam Cipher dan Distribusi Kunci Three-Pass Protocol untuk Mengamankan Data Chatting pada ATmega328 - Budiyanto Budiyanto; Rakhmadhany Primananda; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Arduino devices with ATmega328 microprocessors and NRF24 radio modules can be used as a wireless chat communication devices. Data communication by NRF24 is generally unencrypted, so chat communication is not secure. There are various encryption algorithms that can be used, but not all encryption algorithms are suitable for ATmega328 because of limitations. ATmega328 microprocessor has very limited computational capability, making it less suitable if the encryption process is performed using an algorithm with a high level of computational complexity. Vernam Cipher is an algorithm that uses simple calculations with XOR. Three-Pass Protocol is a simple data transmission protocol that can be used to secure the distribution of encryption keys. In this study, the Vernam Cipher algorithm and Three-Pass Protocol are combined to secure chat data. Chat data that can be secured in this study are text, images, video and audio. From the test results of 10 times on sending chat data, obtained test results with 100% percentage that the system can secure chat data. From the test results, the average time for the encryption process 16 character strings with the Vernam Cipher algorithm on the ATmega328 is 1.9 millisecond.